Multi-Modality guidance based surgical navigation for percutaneous endoscopic transforaminal discectomy. (November 2021) - Pan, Junjun; Yu, Dongfang; Li, Ranyang; Huang, Xin; Wang, Xinliang; Zheng, Wenhao; Zhu, Bin; Liu, Xiaoguang
Highlights: A new AR surgical navigation system for percutaneous endoscopic transforaminal discectomy surgical navigation based on multi-modality guidance. Significantly reduces the frequency of fluoroscopy imaging and lower the radiation risk for both the patient and surgeons. A self-adaptive coordinates calibration and transformation method between different imaging modalities: fluoroscopy, optical tracking, and depth camera. A lightweight non-invasive fiducial with markers coupled with an easy-to-use and efficient algorithm to detect the markers based on YOLO-v3 learning method. Abstract: Objective: Fluoroscopic guidance is a critical step for the puncture procedure in percutaneous endoscopic transforaminal discectomy (PETD). However, two-dimensional observations of the three-dimensional anatomic structure suffer from the effects of projective simplification. To accurately assess the spatial relations between the patient vertebra tissues and puncture needle, a considerable number of fluoroscopic images from different orientations need to be acquired by the surgeons. This process significantly increases the radiation risk for both the patient and surgeons. Methods: In this paper, we propose an augmented reality (AR) surgical navigation system for PETD based on multi-modality information, which contains fluoroscopy, optical tracking, and depth camera. To register the fluoroscopic image with the intraoperative video, we design a lightweight non-invasive fiducial with markers and detect the markers based on the deep learning method. It can display the intraoperative video fused with the registered fluoroscopic images. We also present a self-adaptive calibration and transformation method between a 6-DOF optical tracking device and a depth camera, which are in different coordinate systems. Results: With the substantially reduced frequency of fluoroscopy imaging, the system can accurately track and superimpose the virtual puncture needle on fluoroscopy images in real-time. From operating theatre in vivo animal experiments, the results illustrate that the system average positioning accuracy can reach 1.98mm and the orientation accuracy can reach 1.19 ∘ . From the clinical validation results, the system significantly lower the frequency of fluoroscopy imaging (42.7%) and reduce the radiation risk for both the patient and surgeons. Conclusion: Coupled with the user study, both the quantitative and qualitative results indicate that our navigation system has the potential to be highly useful in clinical practice. Compared with the existing navigation systems, which are usually equipped with a variety of large and high-cost medical equipments, such as O-arm, cone-beam CT, and robots, our navigation system does not need special equipment and can be implemented with common equipment in the operating room, such as C-arm, desktop, etc., even in small hospitals.